Small Molecule Kaempferol Promotes Insulin Sensitivity and Preserved Pancreatic β-Cell Mass in Middle-Aged Obese Diabetic Mice - Hana Alkhalidy; William Moore; Yanling Zhang; Ryan McMillan; Aihua Wang; Mostafa Ali; Kyung-Shin Suh; Wei Zhen; Zhiyong Cheng; Zhenquan Jia; Matthew Hulver; Dongmin Liu (Journal of Diabetes Research)
Insulin resistance and a progressive decline in functional β-cell mass are hallmarks of developing type 2 diabetes (T2D). Thus, searching for natural, low-cost compounds to target these two defects could be a promising strategy to prevent the pathogenesis of T2D. Here, we show that dietary intake of flavonol kaempferol (0.05% in the diet) significantly ameliorated hyperglycemia, hyperinsulinemia, and circulating lipid profile, which were associated with the improved peripheral insulin sensitivity in middle-aged obese mice fed a high-fat (HF) diet. Kaempferol treatment reversed HF diet impaired glucose transport-4 (Glut4) and AMP-dependent protein kinase (AMPK) expression in both muscle and adipose tissues from obese mice. In vitro, kaempferol increased lipolysis and prevented high fatty acid-impaired glucose uptake, glycogen synthesis, AMPK activity, and Glut4 expression in skeletal muscle cells. Using another mouse model of T2D generated by HF diet feeding and low doses of streptozotocin injection, we found that kaempferol treatment significantly improved hyperglycemia, glucose tolerance, and blood insulin levels in obese diabetic mice, which are associated with the improved islet β-cell mass. These results demonstrate that kaempferol may be a naturally occurring anti-diabetic agent by improving peripheral insulin sensitivity and protecting against pancreatic β-cell dysfunction.